Analisis Kesiapan Indonesia dalam Menghadapi Penerapan Pajak Minimun Global Melalui Kebijakan Qualified Domestic Minimun Top-Up Tax (QDMTT) - Najma Sukandi; Ardelia Rahmawati; Putri Alena Hermaliani; Rahma Helmalia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The implementation of the Global Minimum Tax (GMT) through Pillar Two of the OECD/G20 marks a fundamental change in the international tax architecture, especially for developing countries such as Indonesia. One of the key instruments in Pillar Two is the Qualified Domestic Minimum Top-Up Tax (QDMTT), which provides an opportunity for source countries to retain the right to tax the profits of multinational companies with an effective tax rate below 15 percent. This study aims to analyze Indonesia's readiness to face the implementation of GMT through the QDMTT policy, focusing on regulatory aspects and tax administration capacity. The research method uses literature studies with a qualitative-descriptive approach through the analysis of policy documents, tax regulations, as well as academic literature and international reports. The results of the study show that Indonesia's readiness is still in the transition stage. In terms of regulation, Indonesia has shown an initial commitment through the issuance of PMK Number 136 of 2024, but the regulation still needs to be strengthened at a higher level of regulation for long-term legal certainty. From the administrative aspect, the main challenges include the complexity of calculating jurisdiction-based Effective Tax Rates, cross-border data management, as well as increasing the capacity of human resources and information technology infrastructure. This study concludes that the success of QDMTT implementation in Indonesia depends on strengthening regulations, increasing tax administration capacity, and reformulating sustainable investment policies.